ETHOS OF THE STRUGGLE: RACIAL CONSCIOUSNESS AND CULTURAL MEMORY IN THE POETRY OF COUNTEE CULLEN AND NIKKI GIOVANNI (International Journal of Food and Nutritional Sciences, 2022)
The evolution of African-American poetry can be meaningfully traced through the works of Countee Cullen and Nikki Giovanni, two poets separated by generations but united by their deep commitment to Black life, art, and identity. While Cullen represents the refined lyricism and racial duality of the Harlem Renaissance, Giovanni embodies the bold, assertive voice of the Black Arts Movement. Their poetry not only reflects the times in which they lived but also challenges the norms of those times, creating a rich legacy of artistic resistance and cultural expression. This paper presents African Americans' journey and resolve toward their roots. The poetics of identity in the context of racial segregation is remarkably remapped in Countee Cullen's "Heritage" and "Incident." Additionally, it addresses problematic research on colour-line discrimination against enslaved communities and false information about their past. African Americans have been denigrated and estranged from their atavistic culture as a result of the slavery system, which has prevented them from enjoying their identity and human dignity. Here, I want to explore the problem of colour discrimination, which not only affects the African American community but also causes them to lose their cultural identity. This paper mostly examines their estranged status in the midst of America's abundant opportunities for material advancement. Additionally, this essay will examine the race's genealogical research as envisioned by Nikki Giovanni, who supports the identity and dignity of the enslaved community. It is true that the African American people's ancestry traces them back to a time before "the slave trade," when they were content and free, enjoying their language and culture in their atavistic homeland of Africa with human dignity.